Use of formulations for sensitive skin improves the visible signs of aging, including wrinkle size and elasticity - Spada F; Lui AH; Barnes TM (Dove Medical Press, 2019)
Fabrizio Spada, Ada H Lui, Tanya M BarnesResearch & Development, Ego Pharmaceuticals, Braeside, Victoria 3195, AustraliaBackground: Sensitive skin affects an increasingly large proportion of the population and is less tolerant to frequent and prolonged use of cosmetics. This study investigates the antiaging effects of a skin care system developed for use on sensitive skin.Methods: A total of 30 healthy Caucasian females, aged 32–72, were enrolled in this double-blind randomized placebo-controlled split-face study. A routine consisting of twice daily topical applications of the test cleanser and test moisturizer or placebo or positive control products was followed for 28 days, with parameters measured at baseline and at 7-day intervals. Objective skin assessments for hydration, transepidermal water loss (TEWL), skin surface topography, elasticity and safety assessment were conducted.Results: Wrinkle surface, length and depth significantly improved by 34.8±4.7% (P<0.001), 19.0±3.2% (P<0.05) and 24.3±3.5% (P<0.05), respectively, after 28 days of skin care treatment with the test cleanser and test moisturizer. R2 (gross elasticity), R5 (net elasticity) and R7 (biological elasticity) significantly increased by 32.8±6.5% (P<0.001), 47.3±8.6% (P<0.001) and 50.6±5.1% (P<0.001), respectively, while R6 (viscoelastic portion) significantly decreased by 33.4±4.6% (P<0.001) after 28 days. Skin hydration was also found to increase significantly after 28 days by 42.2±8.5% (P<0.01), but there was no change in TEWL. No adverse events were reported.Conclusions: A novel skin care routine developed for use on sensitive skin significantly improves the signs of aging including hydration, wrinkle size and elasticity without significant adverse effects.Keywords: hydration, elasticity, wrinkles, nicotinamide, avenanthramides, vitamin E